Determination of thermodynamical parameters in zone between casting and the die - Bajić, Vladimir; Kovač, Risto; Jojin, Siniša (Journal of Production Engineering, 1992)
This paper is giving contribution to the investigations of the processes which occur during heat transfer between casting and the die with thick wall. The thermodynamical parameters were determined. Primarily, the temperature profit in the intersection of the wall of casting and the die was determined and measurements of the gap size between casting and the die were also carried out. The process was recorded during cooling and solidification of the casting. The relationship which determines the value of the heat transfer coefficient was established and it is based on the use of measured temperatures in the boundary layers of casting and the die, and measured values of the gap size. The heat transfer coefficient as a function of average temperature and the gap size is also presented.